Characterization of Immune Infiltration and Construction of a Prediction Model for Overall Survival in Melanoma Patients - Li, Gang; Zhu, Xuran; Liu, Chao (Frontiers in Oncology, 2021)
The efficiency of anti-programmed cell death/legend-1(PD-1/L1) monoclonal antibody is limited by immunosuppressive tumor microenvironment (TME) of melanoma. Therefore, understanding the complex TME is important to improve immunotherapy. In this study, we used 4 methods to estimate the score of immune cells and analyzed the infiltration pattern of immune cells in primary and metastatic tumor in The Cancer Genome Altas(TCGA) database. We found that a higher infiltration of immune cells in metastatic melanoma. Consensus clustering identified 4 subtypes in melanoma with different immune infiltration. We observed that subtypes with high immune infiltration had a longer overall survival. To further explore underlying mechanisms regarding the immune infiltration, we subdivided the 4 clusters as 2 groups (hot and cold tumor) based on immune infiltration, survival states and predicted immune response. Enrichment analysis of differently expressed genes (DEGs) revealed that hot tumor enriched in immune response. While，tyrosinase related protein1 (TYRP1) over-expressed in cold tumor was negatively correlated CD8A expression in TCGA database and clinical samples. We constructed a predicting model for overall survival using DEGs and validated in our external cohort with ROC at 1, 3, and 5 year were 0.73, 0.77, and 0.81,this model also performed well in predicting survival of patients with immunotherapy treatment. In conclusion, our study provides a deep insight into the immune infiltration in melanoma and the predicting model might guide the clinical treatment of patients with melanoma.